Silent Lung Abscess in a Newborn: A Case Report - Mahmoud Alhandi Omar Helal (16685388) (2023)
Lung abscesses are rare in childhood and very rare in early infancy and neonates. With a predicted incidence of 7 per 1000,000 admissions per year. Furthermore, Neonatal lung abscesses are usually of multi-bacterial etiology. In addition, Risk factors in neonates include prematurity, ventilation, congenital lung malformation, and aspiration. Here, we are reporting a 21 day- old baby, full term, normal vaginal delivery, no history of NICU admission, no resuscitation at birth, group B streptococcus screening is negative, breast feeding, and no respiratory distress at birth, who presented with unusual picture of mild cough and flu without fever or other symptoms, and was diagnosed as a lung abscess, which is probably one of the few cases reported in the literature in neonates. Case presentation: A 3-week-old boy presented with unusual symptoms of cough, flu, without fever, or other manifestations. The Diagnosis of lung abscess was based on chest CT scan. Empirically treated with intravenous antibiotics was started. Then, patient was discharged from the hospital with an outpatient follow-up. At the time of discharge, he had reassuring vital signs and a normal physical examination. At the follow-up visit after one week, no clinical symptoms were reported and the physical examination was normal. Conclusion: unexpected case of lung abscess in neonates is very rare and distinctive condition, so our recommendations for pediatricians are to be vigilant about the silent presentation of infection in neonates. Other information Published in: American Journal of Pediatrics License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://www.sciencepublishinggroup.com/journal/paperinfo?journalid=380&doi=10.11648/j.ajp.20230902.16